Enhanced policy recommendations for sustainable rangeland improvement in Tunisia - CGIAR Research Program on Livestock (2019)
To be implemented more widely, a change in policy is required at the level of the Tunisian Ministry of Agriculture. During a stakeholder workshop in 2018, almost all participants were in favour of this change. In spring 2019, the findings of trials conducted at farm level endorsed our recommendations.